Clinical Genetic Testing for the Cardiomyopathies and Arrhythmias: A Systematic Framework for Establishing Clinical Validity and Addressing Genotypic and Phenotypic Heterogeneity - Garcia, John; Tahiliani, Jackie; Johnson, Nicole Marie; Aguilar, Sienna; Beltran, Daniel; Daly, Amy; Decker, Emily; Haverfield, Eden; Herrera, Blanca; Murillo, Laura; Nykamp, Keith; Topper, Scott (Frontiers in Cardiovascular Medicine, 2016)
Advances in DNA sequencing have made large, diagnostic gene panels affordable and efficient. Broad adoption of such panels has begun to deliver on the promises of personalized medicine, but has also brought new challenges such as the presence of unexpected results, or results of uncertain clinical significance. Genetic analysis of inherited cardiac conditions is particularly challenging due to the extensive genetic heterogeneity underlying cardiac phenotypes, and the overlapping, variable and incompletely penetrant nature of their clinical presentations. The design of effective diagnostic tests and the effective use of the results depends on a clear understanding of the relationship between each gene and each considered condition. To address these issues, we developed simple, systematic approaches to address three fundamental challenges: (1) evaluating the strength of the evidence suggesting that a particular condition is caused by pathogenic variants in a particular gene, (2) evaluating whether unusual genotype/phenotype observations represent a plausible expansion of clinical phenotype associated with a gene, and (3) establishing a molecular diagnostic strategy to address the issue of overlapping clinical presentations. These approaches focus on the systematic evaluation of the pathogenicity of variants identified in clinically affected individuals, and the natural history of disease in those individuals. We applied these approaches to the evaluation of more than 100 genes reported to be associated with inherited cardiomyopathies and arrhythmias including Hypertrophic Cardiomyopathy (HCM), Dilated Cardiomyopathy (DCM), Arrhythmogenic Right Ventricular Dysplasia or Cardiomyopathy (ARVD/C), Long QT Syndrome (LQTS), Short QT Syndrome (SQTS), Brugada, and Catecholaminergic polymorphic ventricular tachycardia (CPVT), and to a set of related syndromes such as Noonan Syndrome and Fabry disease. These approaches provide a framework for delivering meaningful and accurate genetic test results to individuals with hereditary cardiac conditions.